2004
DOI: 10.1159/000076114
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Substance Misuse in Greek Male Prisoners

Abstract: The aim of this survey was to determine levels and severity of self-reported alcohol and drug misuse and associated physical and mental health problems in Greek male prisoners. The sample consisted of 80 randomly selected convicted and remanded male prisoners in a prison in northern Greece. The Mini International Neuropsychiatric Interview (MINI) was used to assess psychiatric disorders including substance abuse and dependence. All prisoners who participated completed the Alcohol Use Disorders Identification T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
3
12
1
1
Order By: Relevance
“…More recently, in a small sample of 80 inmates of the Greek prison in Komotini, with half of the prisoners sentenced, Fotiadou et al [20] found a very high rate of cannabis users (73.8%), and high rates of use of other substances, including, as in our study, frequent use of several drugs. In France, Sahajian et al [14] found 63.1% illicit drug users in Lyon prisons.…”
Section: Use Of Illicit Drugs In Remand Prisonssupporting
confidence: 68%
See 1 more Smart Citation
“…More recently, in a small sample of 80 inmates of the Greek prison in Komotini, with half of the prisoners sentenced, Fotiadou et al [20] found a very high rate of cannabis users (73.8%), and high rates of use of other substances, including, as in our study, frequent use of several drugs. In France, Sahajian et al [14] found 63.1% illicit drug users in Lyon prisons.…”
Section: Use Of Illicit Drugs In Remand Prisonssupporting
confidence: 68%
“…In the study by Fotiadou et al [20] on 80 Greek prisoners, half on remand and half sentenced, 35% claimed to be intravenous drug users.…”
Section: Use Of Illicit Drugs In Remand Prisonsmentioning
confidence: 99%
“…Longitudinal research has established the predictive value of the AUDIT in community populations, where it has been shown to predict future alcohol-related social and medical problems (Conigrave et al, 1995), mortality (Bradley et al, 2001), medication non-adherence (Bryson et al, 2008) and recurrence and persistence of alcohol dependence (Boschloo et al, 2012). In prisons, cross-sectional research has found that between 57% and 81% of prisoners screen positive for harmful alcohol consumption on the AUDIT (Australian Institute of Health and Welfare, 2012;Borrill et al, 2003;Butler et al, 2003;Coulton et al, 2012;Fotiadou et al, 2004;MacAskill et al, 2011;McMurran, 2005;Newbury-Birch et al, 2009;Plant and Taylor, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have explored these factors in DAD prisoners and most were again limited to incoming/remanded prisoners. Among the significant factors are: age, ethnicity [17], childhood conduct disorders, childhood abuse, school difficulties [17,19-22], additional substance-related disorder, previous psychiatric treatment, co-morbid psychiatric diagnosis, psychosis, mood disorder, antisocial personality, self-harm, suicide risk, history of serious illness or injury [16,17,21-23], fewer qualifications, unemployment, housing difficulties [21] and the length of time spent in prison [17]. AAD in prison has been generally ignored, yet alcohol has been widely related to violent behaviour and criminality.…”
Section: Introductionmentioning
confidence: 99%